'Blue Route' for combating climate change. Issue 8 (29th May 2021) - Liu (刘刚), Gang; Qu (曲久辉), Jiuhui; van Loosdrecht, Mark
Abstract : Today's urban water system can be transformed, without big modifications, into a natural and revolutionary "Blue Route" for combating climate change and constructing carbon neutral city, which will lead to self-sustainability of the water sector and supply energy and resources to other sectors.